Analisis Keaktifan Belajar Siswa Selama Pembelajaran Daring pada Masa Covid-19 - Hutasoit, Feronika Aprina; Bangun, Kartini Br; Panggabean, Sarma (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study is to determine the activity of online learning during the covid-19 period and to find out the efforts made in overcoming obstacles to online learning at SD Parulian 2 Medan. The method used in this study is a qualitative method with data collection techniques, namely by means of observation, documentation, and interviews. The results of the study show that there are still some students who do not focus on the online learning system, lack of online learning facilities such as the internet and so on. Then also the unpreparedness of the guardians of students and teachers in facing the online learning. In the implementation of online learning, teachers often use WhatsApp to communicate with students and their parents. In addition, WhatsApp is used by teachers to share information related to learning materials. In conclusion, the implementation of online learning at iSD iParulian i2 Medan was not carried out properly, it can be seen from the results of the study due to the constraints of the lack of active students, limited internet facilities and the use of other learning media besides WhatsApp which is still lacking. The solution to overcome this obstacle is the readiness of parents, such as accompanying children when learning online and providing online learning facilities such as cellphones and internet quota. Keywords: Covid-19, Student Learning Activities, Online Learning